Analisis komponen desain user interface (UI) pada INLISLite di Dinas Perpustakaan dan Kearsipan Kota Lubuklinggau ditinjau dari konsep Schlatter dan Levinson - Lida Dara Jayanti; Sri Rohyanti Zulaikha (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2023)
INLISLite is an innovative program designed by the National Library with the main objective of simplifying the task of librarians in managing collections and facilitating users in the process of borrowing and checking reading availability. One successful implementation of this application can be found at the Lubuklinggau City Library and Archives Office. Despite its status as a public library, the Lubuklinggau City Library and Archives Office remains committed to providing integrated services to the community. Their success is reflected in their A-level accreditation, as well as through active participation in the School Literacy Movement (GLS) program that specifically prioritizes empowering the general public through literacy. This research aims to explore and disseminate knowledge about the ease of use of INLISLite, with the hope that it can be an inspiration for other libraries. The research method used is a literature study, which allows an in-depth understanding of the positive impact and integration of this program in the Lubuklinggau City Library and Archives Office. The results showed that the implementation of the INLIS Lite automation system at the Lubuklinggau City Library and Archives Office has been successful. The principles of User Interface Design proposed by Arifin became the main guide in designing this system, and users responded positively. Even without special training, users were able to operate the system optimally.